BEHAVIORAL DISPLAYED BY MAIN CHARACTER IN THE EIGHTH GRADE FILM DUE TO THE INFLUENCE OF SOCIAL MEDIA - Hajra, Lili; Nur, Muh. Safar; Affandi, Akhmad (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
AbstractThis research discuss about the behavior and the purpose of this study is to analyze the behavior of young people in eighth grade films who experience closed behavior due to technological factors or what we usually called social media. The researchers uses a descriptive qualitative method to explore the behavior displayed by the main character and also to see what factors or impacts have influenced behavior of the main character in the film. Here the researcher takes the object of a film entitled Eighth Grade which was published in 2018. The researcher uses a literary psychology approach. In this thesis, the researchers used Skinner's theory, S-O-R (stimulus organism response). From the results of the study that there are 5 characteristics that indicate that the main character has closed behavior. There are 3 data for stress or anxiety characteristics, 6 data for nervous characteristics, 4 data for slow response characteristics. Then there are 6 data for the characteristics of being alone and finally the characteristics of a nice person, there are 3 data. The researchers used Hakim's theory to classify the behavioral characteristics experienced by Kayla as the main character in the Eighth Grade film. After being classified, the researchers analyzed using the S-O-R theory from Skinner. Then the last one is the factor that causes Kayla to have closed behavior, namely the social media factor. There are positives and negatives. There are 4 data that have a positive impact on Kayla as the main character and there are 7 data from the negative impact that has affected Kayla as the main character. Keywords: Behavior, SocialMedia, EighthGrade, YoungPeople, Film